Evolution of sigma phase in 321 grade austenitic stainless steel parent and weld metal with duplex microstructure. (October 2014) - Green, G.; Higginson, R.; Hogg, S.; Spindler, S.; Hamm, C.
Abstract : Samples of 321 stainless steel from both the parent and welded section of a thin section tube were subjected to accelerated ageing to simulate long term service conditions in an advanced gas cooled reactor (AGR) power plant. The initial condition of the parent metal showed a duplex microstructure with approximately 50% ferrite and 50% austenite. The weld metal showed three distinct matrix phases, austenite, delta ferrite and ferrite. This result was surprising as the initial condition of the parent metal was expected to be fully austenitic and austenite+delta ferrite in the weldment. The intermetallic sigma phase formed during the accelerated ageing was imaged using ion beam induced secondary electrons then measured using computer software which gave the particle size as a function of aging time. The measurements were used to plot particle size, area coverage against aging time and minimum particle spacing for the parent metal. During aging the amount of ferrite in the parent metal actually increased from ∼50 to ∼80% after aging for 15 000 h at 750°C. Sigma has been observed to form on the austenite/ferrite boundaries as they may provide new nucleation sites for sigma phase precipitation. This has resulted in small sigma phase particles forming on the austenite/ferrite boundaries in the parent metal as the ferrite transforms from the austenite.